IMPLEMENTASI TEOLOGI MULTIKULTURAL DALAM PEMBELAJARAN AGAMA DI SMA XAVERIUS BUKITTINGGI - Sarah Anofri; Novi Hendri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the fact that multiculturalism is real, unique, and interesting to study, as well as the processes by which it occurs, creating a safe and peaceful atmosphere. Xaverius High School in Bukittinggi is the only school with a multicultural student population consisting of various ethnicities, such as the Minang, Batak, and Chinese. Furthermore, the students attending the school come from various religions, such as Islam, Catholicism, Protestantism, and others. The type of research used is field research, also known as qualitative research, in which the researcher directly interviews or observes the object of study. The type of research used is descriptive qualitative, which is research that is not intended to test a specific hypothesis, but rather to explain the truth about a variable, phenomenon, or situation. Qualitative methods are a particular tradition in the social sciences that fundamentally rely on observing and relating to humans in their language and terminology. The results of this study are, firstly, the social interactions that exist in SMA Xaverius Bukittinggi such as interfaith communication, tolerance, and cooperation between Islam and Christianity in Bukittinggi. Secondly, the religious learning that exists in SMA Xaverius Bukittinggi. Thirdly, the implementation of multicultural theology in SMA Xaverius Bukittinggi. So, the practices that occur in SMA Xaverius Bukittinggi show that multicultural theology can be implemented in a real and harmonious way in the world of education, especially if all elements of the school have the same vision, namely making diversity a unifying wealth. Theological values ​​of love, justice, and respect for others have become a strong foundation in creating a peaceful, equal, and mutually respectful learning environment.